1975
DOI: 10.1152/ajplegacy.1975.228.3.747
|View full text |Cite
|
Sign up to set email alerts
|

Fate of labeled angiotensin II microinfused into individual nephrons in the rat

Abstract: 14C-labeled angiotensin II ([14C]AII) and tritiated inulin ([3H]In) were infused into individual nephrons in Inactin-anesthetized rats and urinary excretion was measured. Site of infusion was identified by neoprene injection and microdissection. In other experiments with higher doses of [14C]AII, microperfused at 10-4-10-5 M (concentrations 10-5-10-6 higher than contained in plasma), [14C]AII and its urinary metabolites were identified and quantified by two-dimensional peptide mapping. Recovery of 14C was 10.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Consequently one has to be careful with conclusions based on studies with injected ligands. The fact that CT to some extent is taken up and degraded within the cell is different from the degradation pat tern of some other small peptides such as angiotensin [19], bradykinin [20], glucagon (MW == 3,500) [21], and neurotensin [22] which are degraded at the brush border and apparently not taken up to any significant ex tent. The structure of CT containing a ring structure completed by a disulfide bridge is a possible explanation for the greater resistance towards hydrolysis for CT. resulting both in the presence of CT throughout the entire proximal tubule and in a higher extent of in tracellular degradation.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Consequently one has to be careful with conclusions based on studies with injected ligands. The fact that CT to some extent is taken up and degraded within the cell is different from the degradation pat tern of some other small peptides such as angiotensin [19], bradykinin [20], glucagon (MW == 3,500) [21], and neurotensin [22] which are degraded at the brush border and apparently not taken up to any significant ex tent. The structure of CT containing a ring structure completed by a disulfide bridge is a possible explanation for the greater resistance towards hydrolysis for CT. resulting both in the presence of CT throughout the entire proximal tubule and in a higher extent of in tracellular degradation.…”
Section: Discussionmentioning
confidence: 79%
“…The brush border is used as reference since it is the initial binding site, and since the CT bound at this site can be expected to be mainly intact. Any degradation of CT at the brush border is likely to result in the immediate re lease of the degradation products as it is shown for peptides mainly degraded at this site [19][20][21][22]. Therefore, any CT bound to the brush border can be assumed to be intact or consisting of a few large fragments.…”
Section: Discussionmentioning
confidence: 99%
“…4 Previous studies gave little direct evidence that changes in renal hemodynamics and/or glomerular filtration rate could alter the renal handling of angiotensin II. Pullman et al, 7 in a micropuncture study, found that angiotensin II microinfused directly into the tubular lumen was metabolized rapidly by proximal but not by distal tubules of rats. The design of these experiments did not permit assessment of angiotensin II metabolism in the vascular compartment, the susceptibility of circulating angiotensin II to filtration, or the effects of changes in glomerular filtration rate on the total renal metabolism of angiotensin II.…”
Section: Discussionmentioning
confidence: 99%
“…4 Although there are some data to suggest that factors affecting renal hemodynamics may play a role in the intrarenal metabolism of this peptide, the extent to which changes in renal blood flow or glomerular filtration might modify metabolism is unknown.' 1 - 7 The present study was undertaken to determine whether changes in renal hemodynamics or glomerular filtration rate affect angiotensin II metabolism.…”
mentioning
confidence: 99%
“…AT4 receptor is also found in the kidney, where this angiotensin-derived fragment can elicit many responses [55] . Aminopeptidases A and N are abundant in the kidney, especially in proximal nephron, and Ang Ⅳ is formed in the glomerulus [56,57] . Ang Ⅳ increases blood flow in the kidney and decreases in Na + transport in proximal tubules [55] .…”
Section: New Members Of Ras: Ang Ii-derived Peptidesmentioning
confidence: 99%